2012
DOI: 10.1016/j.molcel.2012.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression of Ribosomal Proteins Relieves MicroRNA-Mediated Repression

Abstract: MicroRNAs (miRNAs) regulate physiological and pathological processes by inducing posttranscriptional repression of target messenger RNAs (mRNAs) via incompletely understood mechanisms. To discover factors required for human miRNA activity, we performed an RNAi screen using a reporter cell line of miRNA-mediated repression of translation initiation. We report that reduced expression of ribosomal protein genes (RPGs) dissociated miRNA complexes from target mRNAs, leading to increased polysome association, transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 64 publications
2
23
0
1
Order By: Relevance
“…Similar observations and conclusions were made in worms (Seggerson et al, 2002) as well as in mammals (Kim et al, 2004;Nelson et al, 2004;Maroney et al, 2006;Nottrott et al, 2006;Petersen et al, 2006). However, other studies have shown a shift in the sedimentation of repressed mRNAs from polysome fractions toward lighter fractions (Pillai et al, 2005;Bhattacharyya et al, 2006;Kiriakidou et al, 2007;Ding and Grosshans, 2009;Janas et al, 2012). Moreover, m 7 G-capindependent noncanonical translation, initiated by A-cap or internal ribosome entry sites (IRES), is often immune to miRNAmediated translational repression (Humphreys et al, 2005;Pillai et al, 2005;Wang et al, 2006;Kiriakidou et al, 2007;Mathonnet et al, 2007;Thermann and Hentze, 2007;Wakiyama et al, 2007;Zdanowicz et al, 2009), suggesting translation initiation as the step of miRNA regulation.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Similar observations and conclusions were made in worms (Seggerson et al, 2002) as well as in mammals (Kim et al, 2004;Nelson et al, 2004;Maroney et al, 2006;Nottrott et al, 2006;Petersen et al, 2006). However, other studies have shown a shift in the sedimentation of repressed mRNAs from polysome fractions toward lighter fractions (Pillai et al, 2005;Bhattacharyya et al, 2006;Kiriakidou et al, 2007;Ding and Grosshans, 2009;Janas et al, 2012). Moreover, m 7 G-capindependent noncanonical translation, initiated by A-cap or internal ribosome entry sites (IRES), is often immune to miRNAmediated translational repression (Humphreys et al, 2005;Pillai et al, 2005;Wang et al, 2006;Kiriakidou et al, 2007;Mathonnet et al, 2007;Thermann and Hentze, 2007;Wakiyama et al, 2007;Zdanowicz et al, 2009), suggesting translation initiation as the step of miRNA regulation.…”
Section: Introductionsupporting
confidence: 68%
“…However, the identity and function of pseudopolysomes remain unknown. Moreover, to make things more complicated, previous density gradient analyses have used target mRNAs with a 3 0 poly(A) tail, which are subject not only to pure translational repression but also deadenylation that leads to inhibition at translation initiation (Olsen and Ambros, 1999;Seggerson et al, 2002;Pillai et al, 2005;Bhattacharyya et al, 2006;Maroney et al, 2006;Nottrott et al, 2006;Petersen et al, 2006;Kiriakidou et al, 2007;Mathonnet et al, 2007;Thermann and Hentze, 2007;Kong et al, 2008;Wang et al, 2008;Ding and Grosshans, 2009;Moretti et al, 2010Moretti et al, , 2012Janas et al, 2012). This has caused a typical chickenand-egg problem, making interpretation complicated.…”
Section: Introductionmentioning
confidence: 99%
“…interfere with gene silencing (Huntzinger and Izaurralde, 2011;Janas et al, 2012), the plant mesophyll protoplast system offers the advantages of high amiRNA silencing specificity (see Supplemental Figure 7 online), unlimited AGO activity (see Supplemental Figure 9 online), high cotransfection efficiency (Yoo et al, 2007), highthroughput potential (Li et al, 2011), and broad adaptability in numerous plant species (Sheen, 1991). In particular, our screens can be easily applied to diverse agronomically or pharmacologically important plant species (Figures 6C and 6D).…”
Section: Discussionmentioning
confidence: 99%
“…In animals, luciferase-derived reporters have been widely used in cell-based assays to quantify miRNA activity and have underpinned key studies on miRNA biology (Beillard et al, 2012;Brown et al, 2007;Connelly et al, 2012;Doench and Sharp, 2004;Gibbings et al, 2012;Horman et al, 2013;Huang et al, 2009;Humphreys et al, 2005;Janas et al, 2012;Lytle et al, 2007;Mullokandov et al, 2012;Petersen et al, 2006). Additionally, luciferase-based reporter systems are extensively used to validate miRNA targets in animal cells (Nicolas, 2011).…”
mentioning
confidence: 99%